Profiting from Technological Capabilities: Technology Commercialization Strategy in a Dynamic Context - Simon Wakeman (European School of Management and Technology (ESMT), 2010)
This paper analyzes the technology commercialization strategy of an innovating firm when the incumbent firms possess specialized commercialization capabilities. The predominant framework says that if the innovation is protected by a tight appropriability regime the optimal strategy is to license the innovation to an incumbent firm. Using a game-theoretic model of the technology commercialization process, this paper shows that if the innovating firm has specialized technological capabilities and the ability to learn from its experience in the commercialization process, its optimal strategy may-under certain conditions-be to commercialize alone or to pursue a hybrid whereby it licenses the innovation but retains the rights to participate in the commercialization process. The paper then uses the conditions derived from the model to explain the pattern of technology commercialization arrangements pursued by biotech firms attempting to commercialize 1590 identifiable products in the pharmaceutical industry between 1978 and 2008. The results show that a firm is significantly more likely to use the hybrid strategy when there are more firms competing to license the innovation, when there is a higher probability of commercializing a subsequent product in the same product field in future, and when it is in a stronger financial position.
urn:nbn:de:101:1-2013071912577
Keywords: 650; technology commercialization; biotech; applied game theory; biotechnology; capabilites; innovation; entrepreneurship